Oncologists' experiences caring for LGBTQ patients with cancer: Qualitative analysis of items on a national survey. Issue 4 (April 2021) - Sutter, Megan E.; Simmons, Vani N.; Sutton, Steven K.; Vadaparampil, Susan T.; Sanchez, Julian A.; Bowman-Curci, Meghan; Duarte, Luisa; Schabath, Matthew B.; Quinn, Gwendolyn P.
Highlights: Qualitative analysis of oncologists' experiences with SGM patients with cancer. Oncologists described positive experiences and affirming care practices. Barriers included lack of knowledge, communication apprehension, and microagressions . Oncologists need education in SGM health needs and communication skills. Abstract: Objectives: Sexual and gender minority (SGM) individuals experience cancer-related health disparities and reduced quality of cancer care compared to the general population in part due to a lack of knowledgeable providers. This study explored oncologists' experiences and perspectives in providing patient-centered care for SGM individuals with cancer. Methods: We conducted a qualitative analysis of oncologists' responses to four open-ended items on a national survey eliciting their experiences, reservations, and suggestions in treating SGM patients. Results: Over 50 % of the 149 respondents of the national survey responded to at least one open-ended item. Many oncologists reported positive experiences reflecting personal growth and affirmative care practices, such as open, non-judgmental communication, compassion, competence, and supporting patients' identity. There was a notable lack of experience with transgender patients in particular. Lack of knowledge, interpersonal communication concerns (e.g., fear of offending patients), and microaggressions ("don't ask, don't tell") were identified as barriers to providing affirming care. Conclusions: Oncologists recognize their knowledge deficits and need strategies to overcome communication barriers and microaggressions among the cancer care team to provide SGM-affirming care. Practice implications: Curricula are needed to train oncologists in SGM healthcare needs and affirming communication skills to facilitate patient-centered care for SGM individuals with cancer.